The significance of German as a foreign language in Poland – the results of empirical research on motivation to learn foreign languages - Jakosz, Mariusz (Papers in Linguistics, 2020)
Some statistical data show that Poland takes the leading position in the world when it comes to the number of people learning German as a foreign language, which will be discussed in the introduction of the paper. The results of the research conducted with the use of questionnaires among high school students will be discussed in the further part of the paper. The aim of the research is to distinguish the factors enhancing and diminishing students’ motivation to learn German. Students’ attitudes towards German as a foreign language, teaching materials, text genres and their thematic organization, lesson structures, teacher roles and the affective sphere of learning German are the factors to which the author pays close attention.